The Lyapunov direct method in the theory of asymptotic equivalence of differential equations - Voskresensky , E. V. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
In terms of the Lyapunov direct method sufficient conditions for the asymptotic equivalence of differential equations are given.